Once again about the “Miraculous Power of Waka”. Setsuwa Tales about Poets in the Jikkinsho - N. N. Trubnikova (Russian Japanology Review)
The article deals with the approach to the interpretation of Japanese waka poetry presented in the Jikkinshō collection of setsuwa tales (mid-13th century). The conception of waka in this text proceeds from the words about the miraculous power of poetry in Ki no Tsurayuki’s preface to the Kokinshū anthology (early 10th century). On many examples from the life of Heian poets, the compiler of the Jikkinshō discusses the role of poetry in such spheres as human communication and shintō worship. The compiler examines the relation between various “ways” of realizing one’s talent (waka and kanshi poetry, music, etс). He demonstrates the usefulness of poetic skills in private and public life, the importance of the ability to understand other people’s poetical works and evaluate them judiciously. Relevance and compliance with current circumstances turn out to be the main condition for success in everything that concerns waka, as well as in other worldly affairs.